The Role of Students’ Interests in Self-Regulated Learning: The Relationship between Students’ Interests, Learning Strategies and Causal Attributions - Sorić, Izabela (Array, 2009)
The purpose of this research was to examine the relationship between students' interests, their use of certain specific learning strategies and causal attributions which they made for their academic achievement. In this manner, we attempted to explore the relationships between some important variables from three different, but connected phases of self-regulated learning: the forethought phase (interests), the performance control phase (learning strategies) and the self-reflective phase (causal attributions). Results confirmed the presumption that learning strategies could be a potential mediator in the relationship between students’ interests and their academic achievement. Also, results indicate that the causal dimension of controllability could have a partial mediating role between students’ academic achievement and their interests. Generally, our findings indicate a dynamic and cyclical nature of learning process – interest is an integral part of this process and it could be conceptualized as both a consequence and an antecedent of cognitive aspects of learning.